Role of Coping Skills, Perceived Social Support during Postpartum - Abid Aftab, Ata Ullah, Muhammad Sheraz Afzal Malik, Syed Shah Khalid, Munsif Ali, Sar Sikandar Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The postpartum period is a time that is faced with greater challenges which involve physical, emotional, and social adjustments, these factors can increase vulnerability to psychological distress. Objective: The postpartum period presents a unique psychological challenge for new mothers, encompassing physical recovery, emotional adjustment, and increased social expectations. This study aimed to investigate the relationship between coping skills, perceived social support, and psychological distress during the postpartum period. Method: A correlational research design was employed with a purposive sample of 50 postpartum women (within 40 days post-delivery) recruited from a gynecology department. Inclusion criteria required participants to have completed at least matric-level education and have some form of social support. Data were collected using the Brief COPE Inventory (Carver, 1997), the Multidimensional Scale of Perceived Social Support (Zimet, 1988), and the Kessler Psychological Distress Scale (K10). Statistical analysis was conducted using Pearson product-moment correlation via SPSS v16. Results: The findings revealed that adaptive coping skills were significantly negatively correlated with psychological distress (r = -0.40, p < 0.01), indicating that women who employed adaptive coping strategies reported lower psychological distress. Maladaptive coping showed a positive correlation with psychological distress (r = 0.27). Furthermore, perceived social support exhibited a strong negative correlation with psychological distress (r = -0.51, p < 0.01), confirming its protective role in maternal mental health. Conclusion: The results underscore the importance of both adaptive coping strategies and perceived social support in reducing psychological distress among postpartum women. These findings suggest that interventions enhancing coping skills and strengthening social support networks may improve psychological outcomes during the postpartum period. Keywords: Postpartum period, coping skills, perceived social support, psychological distress, maternal mental health.